2023
DOI: 10.3389/fpls.2022.1058774
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen assimilation and photorespiration become more efficient under chloride nutrition as a beneficial macronutrient

Abstract: Chloride (Cl−) and nitrate (NO3−) are closely related anions involved in plant growth. Their similar physical and chemical properties make them to interact in cellular processes like electrical balance and osmoregulation. Since both anions share transport mechanisms, Cl− has been considered to antagonize NO3− uptake and accumulation in plants. However, we have recently demonstrated that Cl− provided at beneficial macronutrient levels improves nitrogen (N) use efficiency (NUE). Biochemical mechanisms by which b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 106 publications
0
2
0
Order By: Relevance
“…Chlorine (Cl) is classified as a micronutrient, although tissue concentrations are typically in the macronutrient range (>1000 lg g À1 DM), with significant stimulation of biomass production often observed when concentrations are well above 1000 lg g À1 DM (Kopsell & Kopsell, 2015). Cl is assigned with a wide range of beneficial functions in plants, including turgor and osmoregulation, biomass productivity, quality attributes, nitrogen use efficiency, water use efficiency and drought resistance, as well as serving an essential function in the oxygen-evolving complex (OEC) of photosystem II (PSII) (Wege et al, 2017;Franco-Navarro et al, 2019;Raven, 2020;Colmenero-Flores, 2023;Peinado-Torrubia et al, 2023). Vinyard et al (2019) showed that Cl plays an important role in the photoassembly of the OEC by tuning the affinity of various amino acid residues for manganese (Mn).…”
Section: Chlorinementioning
confidence: 99%
“…Chlorine (Cl) is classified as a micronutrient, although tissue concentrations are typically in the macronutrient range (>1000 lg g À1 DM), with significant stimulation of biomass production often observed when concentrations are well above 1000 lg g À1 DM (Kopsell & Kopsell, 2015). Cl is assigned with a wide range of beneficial functions in plants, including turgor and osmoregulation, biomass productivity, quality attributes, nitrogen use efficiency, water use efficiency and drought resistance, as well as serving an essential function in the oxygen-evolving complex (OEC) of photosystem II (PSII) (Wege et al, 2017;Franco-Navarro et al, 2019;Raven, 2020;Colmenero-Flores, 2023;Peinado-Torrubia et al, 2023). Vinyard et al (2019) showed that Cl plays an important role in the photoassembly of the OEC by tuning the affinity of various amino acid residues for manganese (Mn).…”
Section: Chlorinementioning
confidence: 99%
“…Between 2020 and 2035, the global demand for rice is expected to rise from 763 million tons to 852 million tons, necessitating increased production. Nitrogen (N) is a crucial macronutrient for plants, and its availability is a major factor in determining plant growth and production [2]. In fact, N availability is often the major factor limiting crop yields in nutrient-poor soils [3].…”
Section: Introductionmentioning
confidence: 99%